(untitled) (New York, 1960)
The book begins with a general historical survey of ancient civilizations, then goes on to consider such topics as food production, metalworking, building construction, early sources of power, and the beginning of the chemical industry. The second and lengthier portion of the text focuses on the development of the steam engine, machine tools, modern transport, mining coal and metals, the rise of the modern chemical industry, textiles, the internal combustion engine, electricity, and more.
Keywords: Công nghệ,Technology; Lịch sử,History